Care for the drug user: perception of nurses from the Family Health Strategy - Queiroz Subrinho, Lucas; Sena, Edite Lago da Silva; Santos, Vanessa Thamyris Carvalho; Carvalho, Patrícia Anjos Lima de (Saúde e Sociedade, 2018)
This study was based on Maurice Merleau-Ponty’s phenomenology and aimed at understanding how the nurses of the Family Health Strategy perceive the care of drug users at the Primary Healthcare Units (UBS). It was performed at a UBS in Vitória, Espírito Santo, Brazil, in 2015, with eight nurses through a phenomenological interview. The descriptions of the experiences were recorded, transcribed and submitted to the Ambiguity Analysis method. The understanding of the experiences resulted in the category: victim and guilty relation and the (lack of) care of drug users. This study showed that, although the nurses recognize the importance of integral care of drug users, their developed treatment focus primarily on abstinence. And more, they blame these users for the failure of treatment, considering them unresponsive to care, at the same time that they reveal they feel unprepared to care for drug users as they realize the necessity of training. This research points to the need of developing care strategies for drug use that can strengthen the bond between nurses and drug users and promote the rescue of citizenship and respect to drug users.